Migration and hybrid political regimes: Navigating the legal landscape in Russia - Rustamjon Urinboyev (University of California Press, 2021)
While migration has become a vital issue worldwide, mainstream literature on migrants' legal adaptation and integration has focused on cases in Western-style democracies. We know relatively little about how migrants adapt in the ever-growing hybrid political regimes that are neither clearly democratic nor conventionally authoritarian. This book takes up the case of Russia—the third largest recipient of migrants worldwide—and investigates how Central Asian migrant workers produce new forms of informal governance and legal order. Migrants use the opportunities provided by a weak rule of law and a corrupt political system to navigate the repressive legal landscape and to negotiate, using informal channels, access to employment and other opportunities that are hard to obtain through the official legal framework of their host country. This lively ethnography presents new theoretical perspectives for studying legal incorporation of immigrants in similar political contexts.
Keywords: 330; Immigration; Labor; Law and Society